2021
DOI: 10.1128/aac.00418-21
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as a Potential Target for the Development of Prophylactic and Therapeutic Drugs against Schistosoma mansoni Infection

Abstract: Emergence of parasites resistant to praziquantel, the only therapeutic agent, and its ineffectiveness as a prophylactic agent (inactive against the migratory/juvenile Schistosoma mansoni ), makes the development of new antischistosomal drugs urgent. The parasite’s mitochondrion is an attractive target for drug development because this organelle is essential for survival throughout the parasite’s life cycle. We investigated the effects of 116 compounds against Schistosoma man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Although the use of PP as an anthelminthic has dwindled over the years, since the early 2000s, interest in PP has surged due to its potential utilization to target other diseases-causing organisms at every level from viral [ 27 , 28 ] through bacterial [ 29 , 30 , 31 ], plasmodium [ 32 ], and fungi [ 33 , 34 , 35 ] to multicellular organisms [ 36 ] ( Figure 2 ). PP has also shown significant potential in multiple disease types for the ability to reduce toxicity, promote wound repair, and inhibit fibrotic tissue development [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of PP as an anthelminthic has dwindled over the years, since the early 2000s, interest in PP has surged due to its potential utilization to target other diseases-causing organisms at every level from viral [ 27 , 28 ] through bacterial [ 29 , 30 , 31 ], plasmodium [ 32 ], and fungi [ 33 , 34 , 35 ] to multicellular organisms [ 36 ] ( Figure 2 ). PP has also shown significant potential in multiple disease types for the ability to reduce toxicity, promote wound repair, and inhibit fibrotic tissue development [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other clinically used penetrating cations, its mitochondrial localization and targeting are well documented [33]. In particular, it has been shown that pyrvinium inhibits mitochondrial respiration in a parasitic worm [34]. Its mitochondrial accumulation is also responsible for its activity against pathogenic fungi such as Candida auris [35] and Aspergillus fumigatus [36].…”
Section: Pyrvinium and Cyaninementioning
confidence: 95%
“…In contrast, this compound caused a significant reduction in worm and egg burden in early infection (>50%) [48]. Similarly, Talaam et al, (2021), evaluated the possible effect of amiodarone against S. mansoni. In this experiment, amiodarone showed complete inhibition of cercaria motility after 18 hours.…”
Section: Amiodaronementioning
confidence: 99%
“…In the case of schistosomula, after 24 hours with amiodarone, the inhibition of motility was complete. In adult parasites, amiodarone inhibited the motility after 20 hours of incubation was not complete, providing mean motility scores of 0.3 and 1.0 for the male and female, respectively [49]. In in vivo experiments, mice were prophylactically treated with amiodarone (50 mg/kg) by 4 days of once-daily intraperitoneal injection, starting 1 day prior to infection, and then euthanized six days postinfection to recover the schistosomula from the lungs.…”
Section: Amiodaronementioning
confidence: 99%
See 1 more Smart Citation